Automated processing of dense points clouds to automatically determine deformations in highly irregular timber structures. (15th August 2017) - Cabaleiro, M.; Hermida, J.; Riveiro, B.; Caamaño, J.C.
Highlights: Timber beam frequently have irregular cross-sections along their length. Deformation of irregular beams can be automatically determined thanks to LiDAR data. The method was validated in an irregular timber beam under laboratory conditions. The results show that maximum error in the main body of the beam is less than 5%. Abstract: Timber structures frequently present irregular cross-sections along their length, principally in old buildings. This irregularity may be a critical parameter to take into account during the deformation analysis of these structures. The aim of this paper is to propose and develop a new algorithm that automatically estimates the deformations of timber beams that have important geometric irregularities by using laser scanning technology. The proposed algorithm to determine deformations is based on Mohr's Theorems. The method is validated in a beam that is subjected to two different loadings. The results are compared with those obtained by contact methods and the differences are less than 5%. The results obtained demonstrate that the method proposed is suitable for the automatic analysis of deformation in irregular timber structures.